(3ehShYI CMGOjK CMcGe GdeYGedGJ GdeGdjI (B:s (3ehShYI JUfjajI efgLjI abgjI dGMGOjK GdeYGedGJ ef cJH GdSfI (B/s - (3SYjO, geGe YHO GdQMje,s 1944-; (3YHO GdQMje, eMeO geGes ((3GdQjGV (B:s (3LgGO GdCSJGP (B:s (3OGQ GdchKQ,s, 2009)
(3ehShYI JUfjajI efgLjI abgjI dCMGOjK GdeYGedGJ ef cJH GdSfI(B.s
Keywords: (3GdMOjKs -- (3CMcGes -- (3LhGeY Gdafhfs -- (3OhGFQ eYGQas; (3GdeYGedGJ aj GdMOjKs -- (3OhGFQ eYGQas